Beyond the global city: a comparative analysis of cosmopolitanism in middle-class educational strategies in Australia and Brazil. Issue 5 (3rd September 2019) - Windle, Joel; Maire, Quentin
ABSTRACT: The global middle class (GMC) is a theoretical construct that seeks to globalise a set of attributes identified in studies of school choice in the global north, and to a lesser extent in developing nations in Asia. As theorised by Ball a mobile middle class with cosmopolitan sensibilities drives international education options in global cities. This proposition is challenged through analysis of the histories of curriculum and class relations in two national settings (Australia and Brazil) and examination of contemporary class profiles (i.e. economic and cultural properties) in expanding forms of international education in these countries. The paper argues that the forms of cosmopolitanism associated with the educational practices of the GMC must be examined within broader historical relationships of cultural domination. We conclude by arguing that broadening the historical horizon is an important exercise to challenge the claim of the GMC to be a novel category involving exceptional forms of cultural contact generated by the dynamics of the 'global city'.